Promoting a healthy cities agenda through indicators: development of a global urban environment and health index. Issue 1 (2nd January 2018) - Pineo, Helen; Zimmermann, Nici; Cosgrave, Ellie; Aldridge, Robert W.; Acuto, Michele; Rutter, Harry
ABSTRACT: There is a growing awareness among city leaders and policy-makers of the impact of the urban environment on health outcomes and inequalities. Increasingly, practitioners in built environment city departments, such as housing, planning, transport and regeneration, seek new tools and guidance to understand how their respective policies and decisions can support the creation of healthier cities. This paper presents the development of a global index to help city leaders and practitioners understand their role in delivering health outcomes through urban environment policies and programmes. The Building Research Establishment's international Healthy Cities Index (BRE HCI) contains 10 environment categories and 58 indicators, supported by a causal pathways framework. This was achieved through an iterative process including: stakeholder engagement, evaluating research evidence, selecting indicators and identifying data sources. We tested the index and causal pathways approach on two case study cities: Dubai and London. We found that they contributed to: raising awareness of the links between the environment and health; identifying shared responsibilities and the need to work across departmental silos; and uncovering the competing demands faced by some departments (and private sector stakeholders) as they seek to deliver health promoting environments alongside other objectives.